2019
DOI: 10.38150/sajeb.8(6).p223-234
|View full text |Cite
|
Sign up to set email alerts
|

Production and quality assessment of a set-style yogurt fortified with low concentrations of Thymus vulgaris L phenolic extracts

Abstract: The aim of this work was to evaluate the effect of Thymus vulgaris L phenolic extracts (TVPE) on the growth of Streptococcus thermophilus and Lactobacil- lus delbrueckii subsp. bulgaricus, and the impact of their addition in small amounts (2-8%) to a set-style yogurt with regard to variations in physico- chemical, bacteria count and organoleptic properties during 21 days storage at 4°C. The phenolic components were extracted from the crushed aerial parts of the test plant by cold maceration in hydromethanolic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…This could be explained by the decline in the production of exopolysaccharides by the St and Lb lactic ferments, whose proliferation and ability to elaborate these complex carbohydrates in the medium seem to be altered by the phenolic compounds of HEEMP, given that the rheological quality of yogurt, represented mainly by the sticky and cohesive criteria, is proportionally linked to the amounts of exopolysaccharides produced by St and Lb bacteria (Rawsan & Marshal, 1997). Our results are in line with those of several authors who have observed a drop in the rheological quality of yogurts during storage at 4°C, following the antimicrobial effect against these two germs exerted by the phenolic compounds of hydroethanolic extracts of Thymus vulgaris L. (Kheli et al, 2018) and Mentha piperita L. (Ait Chabane et al, 2021), added notably at a high dose of 6%. Moreover, throughout the storage period, yogurts with 2% and 4% HEEMP were better evaluated and appreciated than the control, probably due to the manifestation of a pleasant mixture of odors combining the aromatic components brought by the mint extract, such as menthol, menthone, and limonene (Djenane et al, 2012), and those generated by the fermentative activity of the yogurt bacteria, such as diacetyl, acetaldehyde, and acetone (Beshkova et al, 1998).…”
Section: 4 Yogurt Sensory Analysissupporting
confidence: 93%
“…This could be explained by the decline in the production of exopolysaccharides by the St and Lb lactic ferments, whose proliferation and ability to elaborate these complex carbohydrates in the medium seem to be altered by the phenolic compounds of HEEMP, given that the rheological quality of yogurt, represented mainly by the sticky and cohesive criteria, is proportionally linked to the amounts of exopolysaccharides produced by St and Lb bacteria (Rawsan & Marshal, 1997). Our results are in line with those of several authors who have observed a drop in the rheological quality of yogurts during storage at 4°C, following the antimicrobial effect against these two germs exerted by the phenolic compounds of hydroethanolic extracts of Thymus vulgaris L. (Kheli et al, 2018) and Mentha piperita L. (Ait Chabane et al, 2021), added notably at a high dose of 6%. Moreover, throughout the storage period, yogurts with 2% and 4% HEEMP were better evaluated and appreciated than the control, probably due to the manifestation of a pleasant mixture of odors combining the aromatic components brought by the mint extract, such as menthol, menthone, and limonene (Djenane et al, 2012), and those generated by the fermentative activity of the yogurt bacteria, such as diacetyl, acetaldehyde, and acetone (Beshkova et al, 1998).…”
Section: 4 Yogurt Sensory Analysissupporting
confidence: 93%
“…Furthermore, Khelifi et al. ( 2018 ) demonstrated the antibacterial effect of phenolic extract from Lamiaceae plants, specifically Thymus vulgaris L., against St and Lb , as well as an increase in pH accompanied by a decrease in yogurt acidity as a function of the doses of phenolic extract added during both the fermentation and storage periods. Phenolic compounds exert their antibacterial effects through different modes of action: by damaging the cell walls of bacteria, causing the loss of cellular constituents; by blocking the production of cellular energy; or by destroying the genetic material of bacteria (Yang et al., 2008 ).…”
Section: Resultsmentioning
confidence: 99%
“…All milk batches were inoculated with 3% of a St/Lb leaven mix in a 2:1 ratio. Milk pots were sealed, steamed for 4 h at 45°C, and then refrigerated at 4°C (Arioui et al., 2017 ; Khelifi et al., 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…Comparable results were obtained by Amirdivani and Baba [30], who showed that herbal extracts improved milk fermentation through yogurt bacteria and increased the acidity of yogurts. Khelif et al [31] conducted a study to investigate the effect of thyme extract on LAB growth and concluded that a 2% and 4% addition of thyme extract can be added to yogurts without the risk of deterioration in physicochemical quality or inhibition of lactic bacteria. Bakrm and Salihin [32] found that adding aqueous extract of Ceylon cinnamon and common garlic to goat's milk, cow's milk, and camel's milk had no negative effect on acidification through fermentation.…”
Section: Change In Ph Value During Cream Fermentationmentioning
confidence: 99%